Economic Sustainability of a New Born State - Hoti, Afrim; Bekteshi, Fitore (European Journal of Economics and Business Studies, 2015)
Sustainable development is the concept of a relationship between economic growth and the environment and especially when it comes to a new born country, such as Kosovo. It is naturally important for Kosovo as country, which used to be for a long time with no adequate attention in terms of the economic development under the Yugoslavian political, legal and economic development. Republic of Kosovo is among the richest countries in Europe and wider, seen on the perspective of natural and human resources as well as for geographical position. Nevertheless, the country never had the opportunity to develop itself, using its own resources. Internationally, based on Universal Declaration of Human Rights, International Covenants on Civil and Political Rights as well as the Economic, Social and Cultural Rights, when speaking for self-determination, apart from politics, these documents include the exclusive rights of nations to develop research as well as to orient its country economic resources and economic agenda. Therefore paper aims to present facts on the implication of domestic and international politics in relation to the economic development of a new born country. The analysis will be focused on the policies of Kosovo, as well as activities undertaken in the direction of building an attracting environment in Kosovo for Foreign Direct and Indirect Investments as well as to incite local and international initiatives for business, aiming the general economic growth and the economical sustainability of the state.